PENGARUH USIA DAN PENDAPATAN TERHADAP TINGKAT LITERASI KEUANGAN - Ade Maharini Adiandari; Mahayanti Fitriandari (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of Age and Income on Financial Literacy. The research uses a quantitative approach, where data were collected through a survey involving 149 respondents aged between 18 and 60 years. Data analysis was conducted using SPSS version 22 with validity and reliability tests, normality, multicollinearity, heteroscedasticity and multiple linear regression. The results show that Age and Income have a significant impact on Financial Literacy. Specifically, age contributes more significantly to financial literacy compared to income. Furthermore, both variables have a significant simultaneous effect on financial literacy levels. These findings indicate that age and income factors greatly influence an individual's understanding of personal financial management, which has important implications for financial literacy programs targeting specific age groups and income levels.